Effect of Anterior Horn Tears of the Lateral Meniscus on Knee Stability. Issue 9 (9th September 2022) - Shiwaku, Kousuke; Kamiya, Tomoaki; Otsubo, Hidenori; Suzuki, Tomoyuki; Nabeki, Shogo; Yamakawa, Satoshi; Okada, Yohei; Teramoto, Atsushi; Watanabe, Kota; Iba, Kousuke; Fujie, Hiromichi; Yamashita, Toshihiko
Background: Investigations on the biomechanical characteristics of the anterior horn of the lateral meniscus (AHLM) related to anterior cruciate ligament (ACL) tibial tunnel reaming have revealed increased contact pressure between the femur and tibia, decreased attachment area, and decreased ultimate failure strength. Purpose/Hypothesis: The purpose of this study was to investigate the influence of a complete radial tear of the AHLM on force distribution in response to applied anterior and posterior drawer forces and internal and external rotation torques. We hypothesized that the AHLM plays an important role in knee stability, primarily at lower knee flexion angles. Study Design: Controlled laboratory study. Methods: A total of 9 fresh-frozen cadaveric knee specimens and a robotic testing system were used. Anterior and posterior drawer forces up to 89 N and internal and external rotation torques up to 4 N·m were applied at 0°, 30°, 60°, and 90° of knee flexion. A complete AHLM tear was then made 10 mm from the lateral border of the tibial attachment of the ACL, and the same tests performed in the intact state were repeated. Next, the recorded intact knee motion was reproduced in the AHLM-torn knee, and the change in the resultant force after an AHLM tear was determined by calculating the difference between the 2 states. Results: In the torn AHLM, the reduction in the resultant force at 0° for external rotation torque (34.8 N) was larger than that at 60° (5.2 N; P < .01) and 90° (6.7 N; P < .01). Conclusion: The AHLM played a role in facilitating knee stability against an applied posterior drawer force of 89 N and external rotation torque of 4 N·m, especially at lower knee flexion angles. Clinical Relevance: This study provides information about the effects of AHLM injuries that may occur during single-bundle ACL reconstruction using a round tunnel.